Reconstruction of Multimodal-Based Listening Learning: A Literature Study in the Context of Language and Literature - Widiastari, I Gusti Agung Mas; Dewantara, I Putu Mas; Sutama, I Made; Wirahyuni, Kadek (International Journal of Science and Society, 2026)
Listening is a language skill often considered lacking innovation in teaching practices. Increasingly advanced technology creates opportunities for reconstructing more innovative and adaptive learning by integrating multimodal approaches in audio, visual, and text. This study aims to analyze and reconstruct multimodal-based listening learning in the context of language and literature. The research method used is a literature study, examining various scientific sources that will be used in the research process. The results indicate that multimodal methods can strengthen cognitive engagement, understanding of meaning, and interpretive abilities of students during the listening process. Furthermore, the use of digital media such as podcasts, videos, and interactive platforms has proven effective in creating more relevant learning experiences. This study recommends a multimodal-based listening learning model that is adaptable to technological advances and student needs.